2010
DOI: 10.1021/ie100636f
|View full text |Cite
|
Sign up to set email alerts
|

Steam Reforming of Ethanol over Ni/Al2O3−La2O3 Catalysts Synthesized by Sol−Gel

Abstract: The activity of Ni/Al 2 O 3 -La 2 O 3 catalysts prepared by sol-gel process for hydrogen production using ethanol steam reforming was studied. The effect of Ni and La loading in the reaction activity and hydrogen selectivity was analyzed. The catalytic measurements were performed on a fixed-bed microreactor for a 6 h period; within this time, the catalysts showed partial deactivation. The catalyst containing 12 wt % La showed the highest yield to H 2 , but it also presented the highest deactivation. The other … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
28
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(28 citation statements)
references
References 28 publications
0
28
0
Order By: Relevance
“…Although noble metal catalysts perform well in SRE (particularly Rh-based catalysts, due to its activity for CAC bond breakage [14]), their high cost hardly justifies their practical application. Among the non-noble metal catalysts, Ni and Co are the most studied in the SRE process [15][16][17][18][19][20][21][22][23], showing high CAC bond breakage activity. The main inconvenience in the use of Ni and Co catalysts in hydrocarbons and oxygenates reforming processes is their activity in coke formation, although an increase in steam/ethanol molar ratio and temperature mitigates coke deposition because coke gasification is favored [17].…”
Section: Introductionmentioning
confidence: 99%
“…Although noble metal catalysts perform well in SRE (particularly Rh-based catalysts, due to its activity for CAC bond breakage [14]), their high cost hardly justifies their practical application. Among the non-noble metal catalysts, Ni and Co are the most studied in the SRE process [15][16][17][18][19][20][21][22][23], showing high CAC bond breakage activity. The main inconvenience in the use of Ni and Co catalysts in hydrocarbons and oxygenates reforming processes is their activity in coke formation, although an increase in steam/ethanol molar ratio and temperature mitigates coke deposition because coke gasification is favored [17].…”
Section: Introductionmentioning
confidence: 99%
“…One possible way of obtaining energy from renewable sources involves the fermentation of organic matter to produce bioethanol, which is a low-toxicity liquid that features high power density (8 KWh/kg) and is easy to transport [2]. It has been suggested that instead of using bioethanol in internal combustion engines it could be used to generate hydrogen through steam-reforming reactions for more efficient fuel-cell applications [3,4,5]. An alternative way of producing energy from ethanol has recently been proposed.…”
Section: Introductionmentioning
confidence: 99%
“…The reason may be that La 2 O 3 is much excess and hydrophilic, thus part of the Ni species were easily embedded into La 2 O 3 and covered by La 2 O 3 around it, which prevents part of the Ni species from reducing. [40] To further confirm this, we have performed XRD experiment with the reduced 5Ni/La 2 O 3 -GNC after H 2 -TPR experiment. Apparently, Figure S3 exhibits that a new Ni 2 La 3 O 6.92 phase can be observed besides the metallic Ni phase.…”
Section: H 2 Adsorption-desorption Analysis Of the Reduced Catalysts mentioning
confidence: 81%
“…Whereas, except that the amount of 5Ni/La 2 O 3 ‐GNC (1.11 mmol g cat −1 ) is close to this theoretical value, that of 5Ni/La 2 O 3 ‐PP (0.78 mmol g cat −1 ) and 5Ni/La 2 O 3 ‐TD (0.66 mmol g cat −1 ) is much lower than the theoretical value, indicating some Ni 3+ cations are difficult to be reduced from the LaNiO 3 perovskite crystalline structure, especially in 5Ni/La 2 O 3 ‐PP and 5Ni/La 2 O 3 ‐TD. The reason may be that La 2 O 3 is much excess and hydrophilic, thus part of the Ni species were easily embedded into La 2 O 3 and covered by La 2 O 3 around it, which prevents part of the Ni species from reducing …”
Section: Resultsmentioning
confidence: 99%